Analysis of the focal relationship of level five leadership with school organizational excellence - Hosein Majooni; Siroos Ghanbari (مدیریت و چشم انداز آموزش)
AbstractThe aim of the present study was to investigate the focal relationship of level five leadership with organizational excellence of schools. The statistical population of the research included all the teachers of primary schools in Fars province in the academic year of 2020-2021, numbering 16,264 people. According to the classes of the research society such as the type of region (rich, semi-rich and deprived), the number of cities/districts (39), and gender (male and female) by proportional stratified random sampling method and based on the Cochran formula, a sample of 375 people was selected. The research method is quantitative, descriptive and correlational. Data collection was done based on five-level leadership questionnaire of Cham Asemani (2007), and Organizational Excellence of Amarloo (2018), whose Cronbach's alpha coefficient was 0.96 and 0.91, respectively. In order to analyze the data, descriptive techniques, Pearson correlation matrix, focal correlation analysis, and multiple linear regression were used through SPSS 25 software. The results showed that: the dimensions of level five leadership have a positive and significant focal correlation in alpha of 0.01 with a value of 0.725 with the organizational excellence of schools and are able to explain 464% of the variance of the variable of organizational excellence of schools. Dimensions of manager's personality traits; choosing competent employees, then setting the goal; disciplinary culture; the use of technology and the force density dimension and jump have a positive and significant effect on the organizational excellence variable of schools at the level of 0.01.Extended abstractIntroductionEducational organizations face rapidly changing conditions, because they are placed in an environment that changes rapidly and require innovative and superior capabilities to be able to respond to the challenges of the dynamic environment. Therefore, these organizations want to establish a cycle of continuous improvement, achieve excellence, continuously improve the quality of service delivery, increase the capability of internal elements and human resources, and finally compare themselves with other organizations with the same outline of the organizational excellence model. In this regard, education and training, in sync with other institutions, taking into account its important duties and to face these changes, has measures on its agenda, among which this organization pays attention to the organizational excellence of schools. Organizational excellence guarantees that all parts of the organization work together harmoniously and coherently, and by strengthening and providing the best criteria and methods of self-evaluation and continuous improvement, it helps the progress of organizations. Therefore, the most important management challenge at present is the balanced movement towards improvement and excellence, as well as identifying the factors affecting the organizational excellence of schools. Leadership styles are one of the factors influencing the organizational excellence of schools. Among the leadership styles, level five leadership, as a new perspective for twenty-first century organizations, can be the newest and at the same time, the most practical model that places organizations in the most prominent position of global capitals and assets. Five-level leadership is one of the organizational leadership models mentioned by Collins as the key to the success of organizations. The level five leader is in the highest hierarchy of executive abilities and has all the conditions of the competency pyramid and creates lasting greatness by combining humility and professional will. It is in the light of this leadership style that the excellence of the organization lasts in the long term and the organization does not fall apart when the leader leaves. Considering the importance and necessity of level five leadership and organizational excellence of schools and considering that no research has investigated the mutual relationship between these two variables so far, in this research we are looking for an answer to the question: What is the mutual relationship between level five leadership and organizational excellence of schools, and how do the dimensions of two variables explain and predict each other?Theoretical foundationsToday, leading large and advanced organizations is a difficult task, and this important task requires the efforts of leaders who can, with the help of personality traits, exceptional attractions along with humility, institutionalize the necessary commitment and passion in employees to arouse thoughts, opinions and inspiration to allow them to their expected behaviors. Collins (2001) called this new type of calm and submissive but determined and committed leader "level five leader". The level five leadership model, which today is one of the newest and at the same time the most influential models in large organizations and the utility of great managers of the world, is the result of Jim Collins' five-year research. Collins considers level five leadership to be the key to the success of organizations in moving from good status to excellence. Excellence in the word means rising and being superior, and is a term that is described as the highest order of evaluation. Organizational excellence is the formulation of programs aligned with the organization and its environment, which leads to the excellence of the organization and ensures the process of implementing programs and evaluations of the organization based on comprehensive quality management tools, continuous improvement and organizational learning. In line with the relationship between leadership styles and organizational excellence of schools, Aljaloudi & Battah (2010) in a research mentioned suggestions to increase the use of level five leadership model by managers in schools, which include: providing systems and programs that strengthen the foundations of level five leadership for current and future managers; preparing detailed and standard guidelines, criteria and methods for selecting and hiring school teachers; conducting analytical and realistic studies about the internal and external environment; and also identifying the problems and obstacles in the education department of schools. In a research, McCoy (2011) showed that five-level leadership behaviors help all teachers and students to become more capable and efficient based on Collins' theory and thus go from good to great.Research MethodologyThe present research is quantitative according to the research philosophy, applicable according to the purpose, and descriptive and correlative in terms of the method of data collection and analysis. The research population included all the teachers of primary schools in Fars province in the academic year of 2020-2021, numbering 16,264 people. Considering the classes of the research community based on the number of cities/districts (39), using proportional stratified random sampling and Cochran's formula (at the alpha level of 0.05; error value of 0.05 and the ratio of p and q equal to 0.5), the statistical sample volume was determined to be 375 teachers. The library study method was used in order to collect the theoretical foundations and also the research records of the research topic. The process of gathering the required data was also done online through two questionnaires of level five leadership of Cham Asemani (2007), consisting of 31 items; and schools' organizational excellence of Ammarloo (2018), consisting of 16 items. To analyze the data, statistical techniques were used through SPSS statistical software. Frequency distribution tables, central indices (mean, median and mean), and dispersion indices (standard deviation and variance) were used in the descriptive analysis of the data, and the statistical techniques of Pearson correlation coefficient, focal correlation coefficient, and multivariate regression were used in testing the research hypotheses. Research findingsThe findings related to the first hypothesis of the research showed that the dimensions of level five leadership have a positive and significant focal correlation in alpha of 0.01 with a value of 0.725 with the organizational excellence of schools. Dimensions of manager's personality traits; Choosing competent employees, then setting the goal; disciplinary culture; the use of technology and the force density dimension has a positive and significant effect on the organizational excellence variable of schools at the level of 0.01. The findings related to the second hypothesis of the research showed that the dimensions of level five leadership are able to explain 464% of the variance of the variable of organizational excellence of schools. The dimension of force concentration and jump has the most effect; while the dimension of technology use has the least significant regression effect on the organizational excellence of schools.Conclusion and DiscussionThe purpose of the research was to investigate the focal relationship of level five leadership with the organizational excellence of schools. The results of the research are in agreement with the results of the studies of Qamar & Soomro (2023), Lasrado & Kassem (2021), Al-Dhaafri & Alosani (2021), Rostami alileh et al (2020), Adams, Mooi & Muniandy (2020), Alhefiti, Ameen & Bhaumik (2019), Aljaloudi & Battah (2019), Caldwell, Ichiho & Anderson (2017), Farahbakhsh & Mohammadi (2017). In explaining the results, it can be said that the education authorities pave the way to improve and improve the level of the school by choosing level five leaders for schools that have personality traits such as: internal control center against failure and external control center against success; determination to achieve the goal; professional being of humility and determination. By identifying qualified teachers and then set goals according to them; being bound by discipline and promoting this culture among teachers; encouraging and persuading school colleagues to use technology in carrying out assigned tasks; as well as pooling the ability and improving the performance of teachers; these leaders cause the continuous progress of the school in all dimensions and its organizational excellence. To reach the success in the course of shocking transformations, our country's schools need level five leaders who, with the help of humble personality traits and exceptional charms along with a professional, organized and hard-working spirit, provide the necessary commitment and enthusiasm to achieve the highest level of school performance and excellence. Finally, the following solutions are suggested to the education officials and school managers for the continuous improvement of the quality in all fields and ultimately the organizational excellence of the school: The officials of the education departments should choose leaders for the schools, who, as well as being organized and specialized in the administrative affairs of the school, should be very humble and respectful towards their school teachers so that they can provide a friendly and sincere atmosphere among themselves and the school teachers. In this positive and friendly atmosphere, it is better for school leaders to consult with qualified teachers with an open mind in many matters and ask them for their opinions and help empower and improve them by delegating authority and participating in decisions; it is appropriate that the school leaders compare the current situation and the desired situation of the school by using evaluation and self-evaluation systems, and in this way get an accurate assessment of the extent of the school being on the path of excellence and balanced growth.